English proficiency and learner individual differences: A study of pre-service EFL student-teachers - Mónica Abad; Juanita Argudo; Tammy Fajardo-Dack; Homero Cabrera (Maskana, 2019)
This study examines the relationship between individual factors such as age, learning opportunities, and motivation and English language proficiency of pre-service EFL student-teachers. A background questionnaire and an English proficiency test were given to 121 student-teachers. The results revealed that the majority of participants have a low English proficiency which is not likely to improve at the end of the teaching program and that third language learning as well as integrative motivation are strong predictors of language proficiency. Qualitatively, respondents described their reasons for having English language difficulties and for their integrative and instrumental motivation, which complemented the quantitative data. Suggestions for pedagogical practice that might improve the situation are given.